2020
DOI: 10.1371/journal.pone.0238621
|View full text |Cite
|
Sign up to set email alerts
|

Modelling household well-being and poverty trajectories: An application to coastal Bangladesh

Abstract: Resource-based livelihoods are uncertain and potentially unstable due to variability over time, including seasonal variation: this instability threatens marginalised populations who may fall into poverty. However, empirical understanding of trajectories of household wellbeing and poverty is limited. Here, we present a new household-level model of poverty dynamics based on agents and coping strategies-the Household Economy And Poverty trajectory (HEAP) model. HEAP is based on established economic and social ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 70 publications
0
17
0
4
Order By: Relevance
“…Archetypes are based on qualitative and seasonal quantitative surveys of 1586 households considering their seasonal livelihood combinations and land size (Adams and Adger 2016;Adams et al 2016a). A coping-strategy optimization routine balances incomes, expenditures, assets and savings to approximate the affordable expenditure of the archetypes (Lázár et al 2017). The main limitations of the ΔDIEM concern the livelihoods: landholdings are equiproportionally distributed based on aggregate demographics and land cover changes in a union; there is no household adaptation beyond coping; households react but do not make long-term predictions; service and manufacturing household incomes are input scenarios.…”
Section: The Delta Dynamic Integrated Emulator Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Archetypes are based on qualitative and seasonal quantitative surveys of 1586 households considering their seasonal livelihood combinations and land size (Adams and Adger 2016;Adams et al 2016a). A coping-strategy optimization routine balances incomes, expenditures, assets and savings to approximate the affordable expenditure of the archetypes (Lázár et al 2017). The main limitations of the ΔDIEM concern the livelihoods: landholdings are equiproportionally distributed based on aggregate demographics and land cover changes in a union; there is no household adaptation beyond coping; households react but do not make long-term predictions; service and manufacturing household incomes are input scenarios.…”
Section: The Delta Dynamic Integrated Emulator Modelmentioning
confidence: 99%
“…Simplified, stylized migration assumptions in models can however provide useful comparative insights, and thus, we only consider economic and environmental push factors and remove financial, network, cultural or family barriers to migration. Informed by the existing literature on the impacts of chronic and acute environmental change and locally specific knowledge of coping strategies (Adger et al 2018;Lázár et al 2017), in this application, a household is identified as susceptible to migration and removed from the study area, when any of the following thresholds are exceeded:…”
Section: Scenario Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Masyarakat pesisir adalah salah satu komunitas yang memiliki problematika sosial sendiri, termasuk dalam hal kemiskinan yang sering kali menjadi realita keseharian yang tidak terelakkan (Lázár et al, 2020;Tobey & Torell, 2006). Studi tentang kemiskinan masyarakat pesisir tampak lebih kompleks karena berkaitan dengan faktor sosial dan institusional, tidak hanya isu ekonomi (Mussadun & Nurpratiwi, 2016;Robles-Zavala, 2014) atau berkenaan dengan ketidakkreatifan mereka dalam menjaga keberlangsungan akses atas lingkungan dan sumber daya laut (Glavovic & Boonzaier, 2007;Lawson et al, 2012).…”
Section: Pendahuluan Latar Belakangunclassified
“…Faktor lingkungan memang sangat memengaruhi tingkat kemiskinan di kalangan masyarakat pesisir (Barbier & Hochard, 2019). Gambaran rumah tangga miskin di kawasan pesisir sangatlah kompleks karena selain berkaitan dengan rendahnya tingkat sumber daya manusia, seperti kurang kreativitas dan kemampuan mengelola keuangan, aspek penyebab lain adalah adanya faktor alam yang memaksa mereka untuk bekerja secara musiman (Lázár et al, 2020). Aspek itu juga makin menjerembabkan mereka dalam lubang kemiskinan bilamana terjadi kerusakan atau degradasi lingkungan (Gao et al, 2021;van Wesenbeeck et al, 2015).…”
Section: Ketergantungan Nelayan Terhadap Sumber Daya Lautunclassified